Military service and other socioecological factors influencing weight and health behavior change in overweight and obese Veterans: a qualitative study to inform intervention development within primary care at the United States Veterans Health Administration. Issue 1 (December 2015) - Jay, Melanie; Mateo, Katrina; Squires, Allison P.; Kalet, Adina L.; Sherman, Scott
Abstract Background Obesity affects 37 % of patients at Veterans Health Administration (VHA) medical centers. The VHA offers an intensive weight management program (MOVE!) but less than 10 % of eligible patients ever attend. However, VHA patients see their primary care provider about 3.6 times per year, supporting the development of primary care-based weight management interventions. To address gaps in the literature regarding Veterans' experiences with weight management and determine whether and how to develop a primary care-based weight management intervention to both improve obesity counseling and increase attendance to MOVE!, we conducted a qualitative study to assess: 1) Veterans' personal experiences with healthy weight-related behavior change (including barriers and facilitators to behavior change and experiences with primary care providers, staff, and the MOVE! program), and 2) potential new approaches to improve weight management within primary care at the VHA including goal setting and technology. Methods Overweight/obese VHA patients (aged 18–75, BMI greater than 30 or greater than 25 with at least 1 co-morbidity) were recruited for focus group sessions stratified by gender, MOVE! referral, and attendance. Each session was facilitated by a trained moderator, audio-recorded, and professionally transcribed. Using an iterative coding approach, two coders separately reviewed and coded transcripts, and met frequently to negotiate codes and synthesize emerging themes. Results Of 161 eligible patients, 54 attended one of 6 focus groups (2 female, 4 male, 9–11 participants per session): 63 % were male, 46 % identified as African-American, 32 % White/Caucasian, 74 % were college-educated or higher, and 61 % reported having attended MOVE!. We identified two major themes: Impact of Military Service and Promotion and Sustainability of Healthy Behaviors. After service in a highly structured military environment, Veterans had difficulty maintaining weight on their own. They perceived physical activity as having more impact than diet, but chronic pain was a barrier. We identified individual/interpersonal-, community/environment-, and healthcare system-related factors affecting healthy behaviors. We also received input about Veteran's preferences and experiences with technology and setting health goals. Conclusions Unique factors influence weight management in Veterans. Findings will inform development of a technology-assisted weight management intervention with tailored counseling and goal-setting within primary care at the VHA.